Análisis espacial y temporal el Complejo Cenagoso del Bajo Sinú en épocas secas durante los periodos 2014-2017-2020 en el Departamento de Córdoba, Colombia (2021)
Given the problem that exists in Colombia of wetlands, a spatial and temporal analysis of the Bajo Sinú swamp complex in dry seasons during the periods 2014-2017-2020 in the department of Córdoba Colombia, which is considered one of the most important natural water mirrors of the department, which has been greatly affected in the spatial retreat in dry seasons as the years go by. The methodology used describes the use of Landsat 8 images for dry seasons processed with ERDAS IMAGINE 2014 and Arcmap 10.7 software. with the processes used, the water mirror was dentified in each period and later, when a comparative analysis was performed, the recession suffered by the swamp complex was demonstrated, which in 2014 was 6126,1 ha, then 4871,7 ha in 2017 and finally in 2020 the water mirror was 3840,0 ha.